2011
DOI: 10.1109/jsac.2011.110304
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Distributed Vertical Handoff Strategies in Vehicular Heterogeneous Networks

Abstract: Abstract-This paper addresses the problem of optimal vertical handoff (VHO) in a vehicular network setting. The VHO objective can be minimizing the data transfer time or alternatively minimizing the cost of transmitting traffic. As a framework for performance evaluations, we first analyze a heterogeneous network consisting of a wide-area cellular network interworking with wireless local area networks (WLAN) with fixed interdistance between access points (APs) placed along roadsides. We further analyze a scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 18 publications
0
55
0
1
Order By: Relevance
“…Subsequently it is proved that Session Initiation Protocol (SIP) based IP Multimedia Subsystem registration (IMS) can provide session mobility with optimal service [5]. Optimal vertical handover (VHO) in a vehicular network was proposed recently in 2011 to optimize the cost of transmission [4]. Virtual partitioning with pre-emption technique in cellular/ IEEE 802.16e interworking [6] suggest admission control algorithms through IMS for connection requests considering the class of service (i.e., RT or NRT).…”
Section: Literature Surveymentioning
confidence: 99%
“…Subsequently it is proved that Session Initiation Protocol (SIP) based IP Multimedia Subsystem registration (IMS) can provide session mobility with optimal service [5]. Optimal vertical handover (VHO) in a vehicular network was proposed recently in 2011 to optimize the cost of transmission [4]. Virtual partitioning with pre-emption technique in cellular/ IEEE 802.16e interworking [6] suggest admission control algorithms through IMS for connection requests considering the class of service (i.e., RT or NRT).…”
Section: Literature Surveymentioning
confidence: 99%
“…In integrated networks, there are two types of handoff: intra-technology handoff and intertechnology handoff (Lampropoulos et al, 2005;Shafiee et al, 2011). The intra-technology handoff is traditional Horizontal Handoff (HHO) in which mobile terminals handoff between two adjacent base stations or access points using same access technology.…”
Section: Vertical Handoffmentioning
confidence: 99%
“…However, the vertical handoff from cellular network to WLAN is regarded as a network selection process, because mobile terminals are in a wireless overlay area where both cellular access and WLAN access are available to mobile terminals at same time. Seamless vertical handoffs face challenges caused by the gap between different QoS levels in cellular network and in WLAN Shafiee et al, 2011): UMTS cellular networks provide wide coverage with high QoS provisioning for voice service, but limited-rate data service. However, WLANs support high-rate data service, but lack of universal roaming ability and suffer from low QoS level for voice service, due to their original real-time constraints.…”
Section: Fig 2 Handoffs In Integrated Wlan and Umts Cellular Networkmentioning
confidence: 99%
“…In the existing technical literature, many related studies on VHD have been reported [3,[8][9][10][11][12][13][14][15][16][17][18][19]. In [8], a WLAN to 3G handover decision algorithm was presented based on comparison of the current received signal strength (RSS) and a dynamic RSS threshold when a mobile terminal is connected to a WLAN access point (AP).…”
Section: Introductionmentioning
confidence: 99%